Case report: Emapalumab for active disease control prior to hematopoietic stem cell transplantation in refractory systemic juvenile idiopathic arthritis complicated by macrophage activation syndrome - Chellapandian, Deepak; Milojevic, Diana (Frontiers in Pediatrics, 2023)
Introduction: Macrophage activation syndrome (MAS), a secondary form of hemophagocytic lymphohistiocytosis, is a serious life-threatening complication associated with systemic juvenile idiopathic arthritis (sJIA). MAS is characterized by fever, hepatosplenomegaly, liver dysfunction, cytopenias, coagulation abnormalities, and hyperferritinemia and may progress to multiple organ failure and death. Overproduction of interferon-gamma is a major driver of hyperinflammation in murine models of MAS and primary hemophagocytic lymphohistiocytosis. A subset of patients with sJIA may develop progressive interstitial lung disease, which is often difficult to manage. Allogeneic hematopoietic stem cell transplantation (allo-HSCT) can potentially be a curative immunomodulatory strategy for patients with sJIA refractory to conventional therapy and/or complicated by MAS. The use of emapalumab (anti-interferon gamma antibody) for the active control of MAS in refractory cases of sJIA and associated lung disease has not been reported. Herein we report a patient with refractory sJIA complicated by recurrent MAS and lung disease that was managed with emapalumab and ultimately followed by an allo-HSCT, which resulted in permanent correction of the underlying immune dysregulation and improvement of lung disease. Case Report: We present a 4-year-old girl with sJIA complicated by recurrent MAS and progressive interstitial lung disease. She developed a progressively worsening disease that was refractory to glucocorticoids, anakinra, methotrexate, tocilizumab, and canakinumab. She had a chronic elevation of serum inflammatory markers, notably soluble interleukin-18, and CXC chemokine ligand 9 (CXCL9). Emapalumab, initiated at 6 mg/kg (1 dose) and continued at 3 mg/kg twice weekly for a total of 4 weeks, resulted in MAS remission along with normalization of inflammatory markers. The patient received a matched sibling donor allo-HSCT after a reduced-intensity conditioning regimen with fludarabine/melphalan/thiotepa and alemtuzumab, along with tacrolimus and mycophenolate mofetil for graft-vs-host disease prophylaxis. At 20 months following her transplant, she has maintained a full donor engraftment with complete donor-derived immune reconstitution. She had complete resolution of sJIA symptoms including marked improvement in her lung disease along with normalization of serum interleukin-18 and CXCL9 levels. Conclusion: The use of emapalumab followed by allo-HSCT could help achieve a complete response in refractory cases of sJIA complicated by MAS who have failed standard treatment.